Empowering Women Entrepreneurs through Digital Marketing Adoption: A Path toward Sustainable Business Growth - Windarsari, Wiwin Riski (Malaqbi Publisher, 2025)
This study examines how the adoption of digital marketing empowers women entrepreneurs and contributes to sustainable business growth within micro, small, and medium-sized enterprises (MSMEs). Women entrepreneurs often face socio-cultural, structural, and technological barriers that limit their access to markets, mobility, and decision-making opportunities. In this context, digital marketing provides an alternative pathway for overcoming long-standing constraints by enabling wider market reach, flexible business operations, and increased visibility. Using a descriptive qualitative design, this research examines the experiences, motivations, challenges, and empowerment outcomes of women entrepreneurs in relation to the adoption of digital tools. Data were collected through semi-structured interviews with women-led MSMEs from various sectors and analyzed using thematic analysis. The findings reveal that digital marketing adoption is driven by perceived opportunities for market expansion, consumer behavior shifts, and peer network support. However, entrepreneurs face significant challenges related to digital literacy, access to technology, time limitations, and exposure to online risks. Despite these barriers, digital adoption enhances economic, social, and psychological empowerment by increasing income stability, strengthening professional networks, and improving confidence in technology use. Furthermore, digital marketing supports long-term business sustainability by fostering customer loyalty, enabling innovation, and enhancing resilience during market disruptions. Overall, the study underscores the transformative potential of digital tools for advancing women’s entrepreneurial empowerment and business sustainability, while highlighting the need for targeted capacity-building and supportive digital ecosystems.